FDG PET/CT and Colonoscopy Combine Synergistically in Colorectal Cancer Primary Diagnosis. - Doruk Seyfi; Chuong Bui; Walid Barto; Assad Zahid; Christopher Young (Iranian Journal of Colorectal Research, 2021)
Aim: Colonoscopy is the standard for primary colorectal cancer (CRC) detection, but is invasive and imperfect. The aim of this study was to assess the accuracy of 18F-fluorodeoxyglucose (FDG) Positron emission tomography/Computed tomography (PET/CT) and colonoscopy in the diagnosis of primary CRC. Methods: A retrospective analysis of all patients identified as undergoing a FDG PET/CT scan and a colonoscopy within six months of each other, with no intervening malignancy treatment, over a 12 month period in a single University teaching hospital. Results: Two hundred and sixty-two patients had FDG PET/CT and colonoscopy within 6 months. 206 were excluded for prior treatment. 56 patients were included, 26 (46%) with confirmed primary CRC tumors and 30 (54%) without. Multivariate logistic regression analysis indicated that CRC diagnosis was more likely when colonoscopy was performed before the FDG PET/CT (Odds Ratio (OR) 21.9 (CI 2.6-183) and when CRC was diagnosed on FDG PET/CT (OR 12.3 (CI 3.0-51.0). The ROC-AUC for FDG PET/CT and colonoscopy was 0.81 (CI 0.70-0.93, p <0.001) and 0.96 (CI 0.90-1.0, p <0.001) respectively. Conclusions: Colonoscopy is very good and FDG PET/CT is good as diagnostic tests for CRC primary diagnosis. Together they facilitated diagnosis in all CRC primaries. PET/CT should be considered in patients’ with incomplete colonoscopy where there is suspicion for CRC primary.